Association of GTF2I gene polymorphisms with renal involvement of systemic lupus erythematosus in a Chinese population. Issue 31 (August 2019) - Meng, Yanming; He, Yao; Zhang, Junlong; Xie, Qibing; Yang, Min; Chen, Yuning; Wu, Yongkang
Abstract : Abstract: The purposes of the study was to validate the relationship between General transcription factor II-I (GTF2I) genetic variants and kidney involvements of systemic lupus erythematosus (SLE) patients in a Chinese Han population. Samples from 400 SLE patients and 400 age- and sex-matched healthy controls were collected and genotyped by improved multiplex ligation detection reaction technique. The relationship between gene polymorphism of rs117026326, rs73366469, and susceptibility, progression of SLE were analyzed. The present study provided evidence that rs117026326 and rs73366469 were both associated with SLE susceptibility (both C vs T: P  < .001). The analysis of dominant, recessive disease model provided us with further validation ( P  < .001). Both gene polymorphisms are associated with a triad of disease manifestations among SLE patients. Patients carrying genotype TT of rs117026326 had lower 24-hour urinary total protein (24 hours UTP, g/24 hours), 24-hour urinary protein level (g/L·24 hours), lower frequency of the proteinuria and lupus nephritis (LN). Patients carrying genotype TT at rs73366469 had higher 24-hour urinary protein level, higher frequency of the proteinuria, LN and positive anti-dsDNA than those with other genotypes. This study identified the involvement of GTF2I gene polymorphisms in development of SLE, particularly in renal involvement.